WOMEN IN HIGHER EDUCATION: ASPIRATIONS AND EXPECTATIONS - Tiwari, Anjali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The landscape of gender as an academic discipline is very vast. When we talk about the relationship between education and gender as a part of education, it is revealed that the field itself is very diverse. If we explore the rich literature on gender and education available across the world, it becomes evident that most of the existing literature deals with primary education and there is a dearth of literature crafted in the field of women and higher education. Most of the studies conducted in these fields specifically discuss the problems faced by women in accessing and excelling in higher education. There are very few studies that talk about the aspirations and expectations of society from these educated women and vice versa, i.e. consider the expectations and aspirations of women pursuing higher education themselves. In this paper, the researcher has attempted to understand this very area of higher education of women. In the first section of the paper, the researcher has tried to overview the major trends related to higher education and gender in this field across the world and in the specific context of India. In the next section, the researcher has tried to discuss in detail the various expectations of society from educated women and how this has changed during the course of India's development. For this purpose, the researcher has tried to trace the development of women's higher education in India and the ideology that drives these developmental initiatives.